ANALYSIS OF THE DEVELOPMENT oF ISLAMIC SOCIETY AND ITS RELEVANCE TO THE ROLE oF BKMT (Badan Kontak Majelis Taklim) WEST COAST REGENCY - Gunawan, Gunawan; Ghazali, Bahri; Mukmin, Hasan; Setiawati, Rini (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: The development of Islamic society is a multifaceted and dynamic issue that requires comprehensive study from various perspectives. Organizations such as the Badan Kontak Majelis Taklim (BKMT) play a pivotal role in shaping this process. As the predominant religion in Indonesia, Islam has significantly influenced the character and values of the society. Purpose: This research aims to analyze the development of the Islamic community and its relevance to the role of BKMT in Pesisir Barat Regency. Method: A qualitative approach was used with a case study design, focusing on the BKMT and Taklim Assembly institutions in Pesisir Barat Regency, Lampung Province. Data were analyzed using descriptive techniques, including data collection, reduction, presentation, and conclusion drawing with verification. Result: The results indicate that BKMT functions as an agent of change within the community, positively influencing the mindset and behavior of its members. Implication: Through its activities, BKMT has effectively collaborated with the government in various development programs, positioning itself as a strategic partner in the effort to build a better society. Conclusion: This study emphasizes the significant role of BKMT in the empowerment and development of the Islamic community in the region.